A mild Younger Dryas recorded in southeastern Alaska - Paul S. Wilcox; Sarah J. Fowell; James F. Baichtal (Arctic, Antarctic, and Alpine Research, 2020)
Palynological and sedimentological analyses of lacustrine cores from Baker Island, located in southeastern Alaska’s Alexander Archipelago, indicate that the beginning of the Younger Dryas chronozone, between approximately 12,900 cal yr BP and approximately 12,600 cal yr BP, was cooler and drier than modern conditions, based on decreases in the percentages of Pinus (pine) and Tsuga mertensiana (mountain hemlock) pollen accompanied by increases in Alnus (alder) pollen and fern spores. This initial cool period, lasting only 300 years, was relatively mild compared to the North Atlantic region, with an estimated temperature reduction of approximately 2°C from modern. Further, there is no sedimentological evidence of glaciation within the lake basin during this time interval. A subsequent increase in the percentages of Pinus and Picea cf. sitchensis (Sitka spruce) indicates that conditions ameliorated during the latter portion of the YD, between approximately 12,600 cal yr BP and approximately 11,700 cal yr BP.